Occupational Stress, Burnout and Job Satisfaction among Supervisors in North Cyprus - GÃ¶ker, Suleyman Davut (Richtmann Publishing, 2012)
The demands on supervisors both in and out of educational settings introduced by the recent learner-based innovations andcombined with increased work load have led many to question the levels of job satisfaction, occupational stress and burnout amongsupervisors. The goal of this article was to explore the levels of occupational stress, burnout and job satisfaction among supervisors inNorth Cyprus. The target population of this study was all supervisors working for the Ministry of Education, Youth and Sports in NorthCyprus. All 34 supervisors were included in the study. Data were collected through (1) Occupational Environment Scale (Osipow &Spokane,1983), (2) the Maslach Burnout Inventory (Maslach & Jackson, 1981b) and (3) the Minnesota Work Satisfaction Questionnaire(Weis et al.,1967). The level of job satisfaction of supervisors was found to be high, whereas levels of their occupational stress werefound to be moderate. The levels of emotional burnout and personal accomplishment were also found to be moderate but the level ofdepersonalization was found to be low among the supervisors.